2016
DOI: 10.1177/1558689815607686
|View full text |Cite
|
Sign up to set email alerts
|

Changes in Social Networks and HIV Risk Behaviors Among Homeless Adults Transitioning Into Permanent Supportive Housing

Abstract: Permanent supportive housing (PSH) has been recognized by the U.S. federal government as the ''clear solution'' to chronic homelessness. Whether and how access to PSH affects HIV risk is unclear. This mixed methods pilot study uses a convergent parallel design in order to better understand social relationships and HIV risk during the transition from homelessness to PSH. Findings suggest that (a) Sexual activity and HIV risk behaviors increase with housing, (b) Social network size and composition appear to chan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

10
49
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 27 publications
(59 citation statements)
references
References 43 publications
10
49
0
Order By: Relevance
“…Further, despite an opportunity for enhanced stability and safety for residents, HIV risk behavior does not necessarily decrease after entry into housing among either seronegative (Henwood et al, 2015) or HIV seropositive residents (Aidala, Cross, Stall, Harre, & Sumartojo, 2005; Wolitski et al, 2010). Being homeless is a barrier to sexual intimacy due to limited privacy and shelter policies separating men and women (Brown, Kennedy, Tucker, Golinelli, & Wenzel, 2013).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Further, despite an opportunity for enhanced stability and safety for residents, HIV risk behavior does not necessarily decrease after entry into housing among either seronegative (Henwood et al, 2015) or HIV seropositive residents (Aidala, Cross, Stall, Harre, & Sumartojo, 2005; Wolitski et al, 2010). Being homeless is a barrier to sexual intimacy due to limited privacy and shelter policies separating men and women (Brown, Kennedy, Tucker, Golinelli, & Wenzel, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Being homeless is a barrier to sexual intimacy due to limited privacy and shelter policies separating men and women (Brown, Kennedy, Tucker, Golinelli, & Wenzel, 2013). Having one’s own place may facilitate sexual intimacy, but condom use to prevent sexually transmitted infections (STIs) may decrease once one receives housing (Brown et al, 2012; Brown et al, 2013; Henwood et al, 2013; Henwood et al, 2015). These findings point to the importance of understanding need for HIV prevention among homeless persons entering PSH so that providers can ensure that such services are available to residents during this critical time of transition.…”
Section: Introductionmentioning
confidence: 99%
“…There is a large and growing literature on the use of mixed methods in social research (see Johnson, Onwuegbuzie et al 2007;Greene 2008), with the capacity to shed light on questions of 'real world' or practical significance (Denscombe 2008). Mixed methods have been used in research on housing and homelessness (see, for example, Brown, Kennedy et al 2013), including in pilot projects (Henwood, Rhoades et al 2017). In common with Investigative Panels, these approaches seek to acquire a wide range of information in a short timeframe and provide the context within which more in-depth analyses and discussions may be framed.…”
Section: Research For Discussion Papersmentioning
confidence: 99%
“…Moreover, research that has examined constructs related to mental health among PSH residents, such as substance use (Rhoades et al, a) and quality of life (Henwood, Matejkowski, Stefancic, & Lukens, ), have indicated that social networks are associated with these outcomes, and, as in the case of quality of life, may facilitate positive change (Henwood et al, ). Transitioning into PSH is also a time of social networks change (Henwood et al, ; Rhoades et al, ); however, whether social networks and social network change are associated with improved mental health symptomatology for PSH residents is unknown.…”
Section: Introductionmentioning
confidence: 99%
“…In addition studies have found higher levels of social support to be associated with better mental health functioning among persons experiencing homelessness (Cherner et al, ; Hwang et al, ). Empirical evidence also exists to suggest that social networks change in the transition from homelessness to housing (Henwood et al, ; Rhoades et al, ), but it remains to be seen whether those changes are positive or negative. Existing research of PSH residents has indicated residents have small networks, low social support, and commonly struggle with social isolation (Hawkins & Abrams, ; Padgett, Henwood, Abrams, & Drake, ; Tsai, Mares, & Rosenheck, ; Yanos, Barrow, & Tsemberis, ).…”
Section: Introductionmentioning
confidence: 99%